Can I Trust My Co-worker? Examining Correctional Officers' Perceptions of Staff–Inmates Inappropriate Relationships within a Southern Penitentiary System. Issue 3 (4th March 2018) - Worley, Robert M.; Worley, Vidisha Barua; Hsu, Henda
ABSTRACT: Recently, Joyce Mitchell, a correctional employee in New York, confessed to assisting two dangerous murderers in an elaborate escape attempt. While our study does not focus on correctional officers who admit to such deviant behaviors, it examines correctional officers' perceptions of boundary violations committed by their co-workers. Using a macro-level ecological framework as our theoretical perspective, namely Sampson, Raudenbush, and Earl's (1997) theory of collective efficacy, we surmise that organizational factors such as strong supervision and peer support can build mutual trust in prison environments where correctional officers perceive their jobs to be dangerous and stressful. Our findings have important implications for the management of correctional facilities as well as for the contemporary development and significance of the theory of collective efficacy.